1999
DOI: 10.1002/(sici)1096-8628(19990820)88:4<311::aid-ajmg6>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphism-diet-cofactor-development hypothesis and the gene-teratogen model for schizophrenia and other developmental disorders

Abstract: Three problems in identifying genes causing schizophrenia and other developmental disorders may be locus heterogeneity, high disease allele frequency, and unknown mode of inheritance. The DNA polymorphism-diet-cofactor-development (DDCD) hypothesis addresses the first two. The gene-teratogen model addresses the third. The DDCD hypothesis is that schizophrenia results in part from brain abnormality in utero from the aggregate effect of multiple mutations of small effect of genes related to important cofactors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 154 publications
0
12
0
Order By: Relevance
“…The PAH STR is roughly 50 Kb from PAH, and its alleles are in LD with variants in PAH, at least in those populations examined (Goltsov et al 1993). There is some literature tying maternal PAH levels, especially phenylketonuria, to liability to Scz in offspring (see Johnson 1999 for review); there is also some evidence, however, for association in the affected generation with PAH STR alleles (Wilcox et al 2002) and PAH variants themselves (Richardson et al 2003). The clustering of association results in 17q23.2-23.3 occurs for the same loci that show two-point linkage to narrow and broad (true) diagnosis in these pedigrees (Klei et al 2005), as well as moderate associations with diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The PAH STR is roughly 50 Kb from PAH, and its alleles are in LD with variants in PAH, at least in those populations examined (Goltsov et al 1993). There is some literature tying maternal PAH levels, especially phenylketonuria, to liability to Scz in offspring (see Johnson 1999 for review); there is also some evidence, however, for association in the affected generation with PAH STR alleles (Wilcox et al 2002) and PAH variants themselves (Richardson et al 2003). The clustering of association results in 17q23.2-23.3 occurs for the same loci that show two-point linkage to narrow and broad (true) diagnosis in these pedigrees (Klei et al 2005), as well as moderate associations with diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45] These factors also appear to have an association with low folate. 38,41,46 With respect to the late winter/early spring births, the low folate intake, secondary to decreased supplies of folate-rich foods commencing in the autumn, would occur during the second trimester of the pregnancy. 46 This period is also implicated in a study by Opler and colleagues, 47 which suggested an association between schizophrenia and high second-trimester maternal δ-aminolevulinic acid (δ-ALA) levels.…”
Section: Evidence For Neurodevelopmental Basis To Schizophreniamentioning
confidence: 99%
“…38,41,46 With respect to the late winter/early spring births, the low folate intake, secondary to decreased supplies of folate-rich foods commencing in the autumn, would occur during the second trimester of the pregnancy. 46 This period is also implicated in a study by Opler and colleagues, 47 which suggested an association between schizophrenia and high second-trimester maternal δ-aminolevulinic acid (δ-ALA) levels. δ-ALA is a marker for lead exposure, which, like folate, is also associated with poor urban settings, 48 though not with many of the other factors listed above.…”
Section: Evidence For Neurodevelopmental Basis To Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations